(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2026)
The research was conducted in the Care and Storage Laboratory, Department of Horticulture and Garden Engineering at the College of Agricultural Engineering Sciences- University of Baghdad, Jadriyah, during the growing season 2022-2023 to determine the effect of storage temperature on the flowering and Vase life of rose flowers treated with organic and bio-fertilizers. The experiment was conducted after completing all measurements related to both vegetative and flowering growth. Flowers were harvested at the half-open bud stage (when 3 of the sepals leaves are open), which is the appropriate stage for harvesting flowers. The flowers were placed in similar containers with equal volumes of distilled water supplemented with 5 gl-1 an aspirin tablet containing the active substance salicylic acid. The containers were stored for 5 days in refrigerators at a temperature of ±4°C and then continued storage at room temperature until the end of the vase life. The average results for the treatments showed that treatment T5 gave the highest relative fresh weight and water uptake rate at 110.1% and 3.647 g per stem per day, respectively. Treatment T14 showed the lowest water loss rate at 2.44 g stem-1 day-1, followed by treatments T7 and T30. Treatment T6 showed the highest vase life for stored flowers at 12.33 days, followed by treatments T23 and T14. The control treatment had the lowest values for all treatments included in the study.